Understanding the Role of Personality and Emotional Factors in Learners' Metacognitive Performance in Mathematics - Amanah, Atika; Djadir, Djadir; Wahyuni, Maya Sari (Journal La Edusci, 2024)
The research analyzes how metacognitive awareness and Five-Factor Model based personality traits and anxiety degrees affect students' mathematical problem-solving performance. The study used SEM with SmartPLS to gather data from secondary school students who answered self-assessment questionnaires consisting of MAI, BFI and STAI. Student performance in problem-solving improves notably when they possess advanced metacognitive abilities because they effectively use planning and evaluation alongside monitoring of their cognitive approaches. People who are open to new experiences along with those who are conscientious show stronger metacognitive abilities which supports their problem-solving effectiveness. Research discoveries revealed that enhancing anxiety raises obstacles to metacognitive processing that results in reduced academic performance among students in mathematics. The research showed personality traits and anxiety independently affect metacognition but failed to identify any direct influence between these constructs. Educational strategies should focus on building metacognitive capabilities and anxiety control systems because studies indicate they will boost mathematical performance outcomes. This investigation demonstrates how personalized educational strategies that regard individual personality characteristics might deliver positive outcomes.